Increased mean platelet volume and immature platelet fraction as potential predictors of thrombotic complications in BCR/ABL-negative myeloproliferative neoplasms - Kissova, Jarmila; Bulikova, Alena; Ovesna, Petra; Bourkova, Ludmila; Penka, Miroslav (International journal of hematology, 2014)
BCR/ABL-negative myeloproliferative neoplasms (MPNs) are considered to be acquired thrombophilic conditions. Persistently enhanced platelet activation has been described in polycythaemia vera and essential thrombocythaemia (ET), and shown to contribute to a higher risk of arterial and venous thrombotic complications. Recent studies have shown that mean platelet volume (MPV) and immature platelet fraction (IPF) can serve as useful markers of platelet activation and increased risk of thrombosis. The aim of the present study was to investigate the relationship between these parameters and thrombotic events in BCR/ABL-negative MPN. MPV values in patients with BCR/ABL-negative MPN were significantly higher than MPV values of healthy individuals (P < 0.001). No significant difference in MPV or IPF was observed between groups of patients with and without thrombotic complications (P = 0.441; P = 0.110); the difference in IPF values was close to the significance level for patients with ET (P = 0.073). Higher values of IPF were more frequently detected in patients with JAK2 V617F positivity (P = 0.030). These patients had higher MPV more frequently than others, and this difference was close to the significance level (P = 0.056). Further studies should validate the use of platelet parameters to identify patients at high risk.
Keywords: mutace; dospělí; Female; myeloproliferativní poruchy; Adult; střední objem trombocytu; ženské pohlaví; trombocyty; bcr-abl fúzní proteiny; Quinazolines; lidé; trombóza; Platelet Aggregation Inhibitors; Mutation; studie případů a kontrol; Blood Platelets; Myeloproliferative Disorders; Risk Factors; Male; Case-Control Studies; Aged; chinazoliny; Thrombosis; rizikové faktory; inhibitory agregace trombocytů; Mean Platelet Volume; lidé středního věku; senioři; mužské pohlaví; Janus Kinase 2; Fusion Proteins, bcr-abl; Janus kinasa 2; Middle Aged; Humans